The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.neurobiolaging.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction precedes neurodegeneration in mahogunin (Mgrn1) mutant mice

Abstract: Oxidative stress, ubiquitination defects and mitochondrial dysfunction are commonly associated with neurodegeneration. Mice lacking mahogunin ring finger-1 (MGRN1) or attractin (ATRN) develop age-dependent spongiform neurodegeneration through an unknown mechanism. It has been suggested that they act in a common pathway. As MGRN1 is an E3 ubiquitin ligase, proteomic analysis of Mgrn1 mutant and control brains was performed to explore the hypothesis that loss of MGRN1 causes neurodegeneration via accumulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 45 publications
5
43
0
Order By: Relevance
“…Independently of whether mitochondrial dysfunction is a cause or consequence of neurodegeneration (Sun et al, 2007;Bogaerts et al, 2008), our results suggest that inflammation-induced i-mtNOS is probably related to mitochondrial failure in the MPTP model of PD (Przedborski et al, 2004). In fact, MPTP reduced complex I activity by 48% and 29% in SN and ST, respectively, and this different degree of inhibition agrees well with the different i-mtNOS activity and oxidative/ nitrosative stress observed in SN and ST mitochondria of mice treated with MPTP.…”
Section: Discussionsupporting
confidence: 82%
“…Independently of whether mitochondrial dysfunction is a cause or consequence of neurodegeneration (Sun et al, 2007;Bogaerts et al, 2008), our results suggest that inflammation-induced i-mtNOS is probably related to mitochondrial failure in the MPTP model of PD (Przedborski et al, 2004). In fact, MPTP reduced complex I activity by 48% and 29% in SN and ST, respectively, and this different degree of inhibition agrees well with the different i-mtNOS activity and oxidative/ nitrosative stress observed in SN and ST mitochondria of mice treated with MPTP.…”
Section: Discussionsupporting
confidence: 82%
“…TAL (also known as LRSAM1) and MDM2 are two different E3 ubiquitin ligases, which are involved in the ubiquitinylation of TSG101 protein [38][39][40]. MGRN1 null mutants exhibit problems in pigmenttype switching, induce oxidative stress, and show mitochondrial dysfunction preceding neurodegeneration [41,42].…”
Section: Molecular Functions Of Mgrn1 In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Although recent studies have suggested that MGRN1 has a role in oxidative stress (Sun et al, 2007;Chhangani and Mishra, 2013), the molecular basis for these observations was elusive.…”
Section: Introductionmentioning
confidence: 99%